Proposing a THz refractive index sensor based on the excitation of SPPs with an InSb cylinder - Sajedeh Zamani Noughabi; Amir Saman Nooramin; Mohammad Soleimani (AUT Journal of Electrical Engineering)
A novel metamaterial absorber sensor has been proposed for refractive index measurement in the range of [1-2] for the THz frequency band. This structure is based on using a plasmonic coaxial resonator which is excited by an InSb cylinder. Surface Plasmon Polaritons (SPPs) are excited on the surface of the InSb cylinder due to an inward plane wave and propagate downward toward the cavity and through it. Based on the radius and height of the InSb cylinder, the “high-absorption” and “high-quality factor” sensing performance is introduced and analyzed. It is shown that nearly 98% absorption can be achieved for all the range of refractive index [1-2] at 1.8622 THz and in the case of “high-quality factor”, absorption reaches nearly 100% for the refractive index range of [1.5-2]. Also, by changing the radius and height of the cavity, absorption can be changed. Furthermore, sensitivity, quality factor, and figure of merit in the range of 166-672 GHz per refractive index unit (GHz/RIU), 69.1-118.7 and 10.2-29.7 is achievable, respectively. A wide range of refractive index measurements besides superior sensing performance made this structure a good candidate for sensing applications such as medical and biological applications.